Increased Cortical Porosity in Older Men With Fracture. (21st May 2015) - Sundh, Daniel; Mellström, Dan; Nilsson, Martin; Karlsson, Magnus; Ohlsson, Claes; Lorentzon, Mattias
ABSTRACT Cortical porosity increases with age and affects bone strength, but its association with fracture in older men is unknown. The aim of this study was to investigate whether cortical porosity is associated with prevalent fractures in older men. A subsample of 456 men aged 80.2 ± 3.5 (mean ± SD) years, with available high‐resolution peripheral quantitative computed tomography measurements at the tibia from the 5‐year follow‐up exam, was drawn from the prospective MrOS Gothenburg study. Dual‐energy X‐ray absorptiometry was used to measure areal bone mineral density (aBMD). Data on physical activity, calcium intake, medications, diseases, and smoking were collected on questionnaires at the follow‐up exam. Of 87 men (19.1%) with fracture at or after age 50 years (all fracture group), 52 (11.4%) had had a self‐reported fracture before the baseline exam and 35 (7.7%) had had an X‐ray–verified fracture between baseline and follow‐up. Men in the all‐fracture group and in the X‐ray–verified group had 15.8% (13.2% ± 4.9% versus 11.4% ± 3.8%; p < 0.001) and 21.6% (14.1% ± 5.2% versus 11.6% ± 3.9%; p < 0.01) higher cortical porosity, respectively, than men in the nonfracture group. The independent associations between bone microstructure parameters and fracture were tested using multivariate logistic regression with age, height, weight, calcium intake, smoking, physical activity, medications, and diseases as covariates. Cortical porosity was independently associated with any fracture (reported or X‐ray–verified; OR per SD increase 1.49; 95% confidence interval (CI), 1.17 to 1.90) and with any X‐ray–verified fracture alone (OR 1.73; 95% CI, 1.23 to 2.42). Including aBMD (spine or hip, respectively) in the multivariate logistic regression above revealed that cortical porosity was associated with any fracture (OR 1.54; 95% CI, 1.17 to 2.01) and with X‐ray–verified fracture alone (OR 1.49; 95% CI, 1.00 to 2.22). Cortical porosity was associated with prevalence of fracture even after adjustment for aBMD. © 2015 American Society for Bone and Mineral Research.